Management of angular cheilitis in children - Fajriani Fajriani (DiscoverSys Inc., 2017)
Objective : Angular cheilitis is a type of oral soft tissue disease that can occur in children and adults, the condition is characterized by cracks and inflammation on both corners of the mouth. Although this disease can not cause severe disorder, it quite disturbs one's activity and physical appearance. Mild Angular cheilitis will recover itself over times. However severe conditions can cause pain and bleeding. This paper aims to inform colleagues about management of angular cheilitis in children.